Immunomodulatory Role of Plants and Their Constituents on the Management of Metabolic Disorders: An Evidence-Based Review - Febriyanti RM; Levita J; Diantini A (Dove Medical Press, 2024)
Raden Maya Febriyanti,1,* Jutti Levita,2,* Ajeng Diantini2 1Department of Biology Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia; 2Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idAbstract: The relationship between the immune system and metabolic diseases is complex and increasingly recognized as critical to understanding conditions like obesity, diabetes, and cardiovascular diseases. Modulation of the immune system in patients with metabolic disorders can offer several potential benefits. While the salutary impact of plant-derived bioactive compounds on metabolic and immune functions is acknowledged, there is a paucity of comprehensive reviews on the multifaceted and synergistic mechanisms through which these effects are mediated. This review elucidates the therapeutic potential of phytochemical formulations in ameliorating metabolic disorders and delineates their mechanistic implications on relevant biomarkers and immune modulation. Our analysis reveals a predominance of plant species, including Boswellia serrata, Cinnamomum cassia, Citrus bergamia, Coffea arabica, Ficus racemosa, Momordica charantia, Morus Alba, and Trigonella foenum-graecum, that have undergone clinical evaluation and have been substantiated to confer both metabolic and immunological benefits. The phytoconstituents contained in these plants exert their effects through a range of mechanisms, such as improving glucose regulation, reducing inflammatory responses, and modulating immune system. As such, these findings hold considerable promise for clinical and therapeutic translation and necessitate further empirical validation through randomized controlled trials and mechanistic elucidations to affirm the safety and efficacy of herbal formulations.Keywords: metabolic disease, immune system, phytoconstituents